2019
DOI: 10.1111/jvh.13148
|View full text |Cite
|
Sign up to set email alerts
|

B.A.R.C.O.S. (Brazilian Argentine Hepatitis C Collaborative Observational Study): Effectiveness and clinical outcomes of HCV treatment with daclatasvir and sofosbuvir with or without ribavirin

Abstract: Real-world data evaluating the effectiveness of direct-acting antivirals (DAAs) in hepatitis C virus (HCV) treatment have been reported from different regions. Our aim was to evaluate the effectiveness and clinical outcomes of daclatasvir (DCV) and sofosbuvir (SOF) ± ribavirin (RBV) in a prospective multicentre cohort study including patients from Argentina and Brazil who received DCV/SOF ± RBV for 12 or 24 weeks from 2015 to 2018. Multivariable logistic regression models were carried out to identify factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…It is noteworthy that some of these studies generated their findings from either a clinical trial or a structured treatment accessibility program (12)(13)(14)(15). A few of them were undertaken in settings in which the sofosbuvir-daclatasvir combination only served as an option among many others (16)(17)(18)(19)(20)(21)(22)(23), while the rest presented the data limited to specific populations, HCV genotypes and liver cirrhotic status (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…It is noteworthy that some of these studies generated their findings from either a clinical trial or a structured treatment accessibility program (12)(13)(14)(15). A few of them were undertaken in settings in which the sofosbuvir-daclatasvir combination only served as an option among many others (16)(17)(18)(19)(20)(21)(22)(23), while the rest presented the data limited to specific populations, HCV genotypes and liver cirrhotic status (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…The introduction of DAAs in Latin America was later than in Europe, Asia, and North America, but it achieved similar successful results in terms of viral eradication in real‐life studies. ( 2‐4 )…”
mentioning
confidence: 99%
“…Finally, screening and full‐text assessment resulted in 20 included studies (14 manuscripts and 6 conference abstracts) that reported on SVR12 by DAAs in 7,393 individuals from South American countries (Figure 1). 27‐46 A total of 16 studies were published in English, two in Spanish 40,44 and two in Portuguese 29,33 . In addition, included studies were performed in Brazil (n = 11), Argentina (n = 4), Chile (n = 1), Colombia (n = 1), Peru (n = 1), and international collaborations in South America (n = 2) [Argentina, Chile, Colombia and Uruguay (n = 1); Argentina and Brazil (n = 1)].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, screening and full-text assessment resulted in 20 included studies (14 manuscripts and 6 conference abstracts) that reported on SVR12 by DAAs in 7,393 individuals from South American countries ( Figure 1). [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] A total of 16 studies were published in English, two in Spanish 40,44 and two in Portuguese. 29,33 In addition, included studies were performed in Sofosbuvir/Simeprevir ± Ribavirin (SOF/SIM ± RBV), Sofosbuvir/ Ledipasvir (SOF/LDV) or Ombitasvir/Paritaprevir/Ritonavir + Dasa buvir ± Ribavirin (OBV/PTV/r/DSV ± RBV).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%